A Society for Professional Archaeologists in Tanzania: A Call for Action - Bigambo, Richard (Zamani: A Journal of African Historical Studies, 2024)
This essay discusses the need for an Archaeological Association of Tanzania and provides its general structure. It argues that the proposed association is essential for promoting the country’s development, heritage preservation and conservation, and promotion of archaeological studies. In addition to providing resources and support for research, training, and education, it would facilitate collaboration and networking, help protect and preserve Tanzania's cultural heritage, and increase public awareness and education about archaeology in Tanzania. The essay also discusses the development of archaeology in Tanzania and the history and contributions of archaeological associations worldwide. This structure for the proposed association would enable the association to effectively promote archaeology throughout the country through public awareness and education.